Carbonic Anhydrases III and IV Autoantibodies in Rheumatoid Arthritis, Systemic Lupus Erythematosus, Diabetes, Hypertensive Renal Disease, and Heart Failure - Chengeng Liu; Yue Wei; Jianmin Wang; Langan Pi; Jianjun Huang; Peichang Wang (Clinical and Developmental Immunology)
In the present study, the CA III and IV autoantibodies, CA activity, antioxidant enzymes and cytokines in rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), diabetes, hypertensive renal disease, and heart failure were investigated. The anti-CA III antibody titers in patients with RA, SLE, and type 1 diabetes (T1D) were significantly higher than that in control groups (P<0.05). The anti-CA IV antibody titers in patients with RA, SLE, type 1 diabetic nephropathy (T1DN), and heart failure were significantly higher than that in control groups (P<0.05) while anti-CA IV antibody could suppress the total CA activity. The SOD and GPx levels in patients with RA, SLE, and T1DN were significantly lower than that in control groups (P<0.05). IL-6, IL-17, IFN-γ, and TNF-α levels were significantly higher in SLE group compared with the control group (P<0.05). Weak but significant correlations were found between anti-CA III antibodies and ESR in RA (r=0.403, P=0.013) and SLE patients (r=0.397, P=0.007). These results suggested that the generation of CA III and IV autoantibodies, antioxidant enzymes, and cytokines might influence each other and CA autoantibodies might affect the normal physiology function of CA.